PERAN RELIGIUSITAS DALAM MENGELOLA KECEMASAN AKADEMIK MAHASISWA: STUDI KUALITATIF PADA REMAJA PUTRI DI PONDOK PESANTREN - Sindi Aprilia Putri; Lailatul Fitriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of religiosity in managing academic anxiety among female adolescent university students living in Islamic boarding schools. This research employed a descriptive qualitative approach using purposive sampling techniques involving students who experienced academic anxiety. Data were collected through interviews, observations, and documentation, and were analyzed descriptively to gain an understanding of the participants’ subjective experiences. The findings indicate that academic anxiety frequently arises when students face academic demands such as assignments, examinations, presentations, and thesis writing. The anxiety is characterized by physical and emotional symptoms, including insomnia, rapid heartbeat, restlessness, overthinking, fear of failure, and lack of self-confidence. The factors contributing to academic anxiety stem from both internal and external aspects, such as low self-confidence, the tendency to compare oneself with others, high academic demands, and the intensive activities within the boarding school environment. Furthermore, the study found that religiosity plays a significant role in helping students manage academic anxiety through religious practices such as prayer, supplication, dhikr, and recitation of the Qur’an. Religious values, including tawakal (trust in God), patience, and earnest effort (ikhtiar), contribute to inner peace, enhance learning motivation, and assist students in coping with academic pressure in a more positive and adaptive manner.